2020
DOI: 10.1007/s40617-020-00488-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior-Analytic Approaches to the Management of Diabetes Mellitus: Current Status and Future Directions

Abstract: Diabetes mellitus is the seventh leading cause of death in the United States, requiring a series of complex behavior changes that must be sustained for a lifetime (e.g., counting carbohydrates, self-monitoring blood glucose, adjusting insulin). Although complex, all of these tasks involve behavior, making them amenable targets for behavior analysts. In this article, the authors describe interventions that have focused on antecedent, consequent, multicomponent, and alternate procedures for the management of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 122 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…In addition to the special series on public health in this journal, a 2019 special issue of Perspectives on Behavior Science focused on addictions, and showcased substantial basic, translational, applied, and public health contributions of behavior analysis (Washington & Galizio, 2019). Recent conceptual and empirical work has focused on diabetes prevention and management (Raiff et al, 2020), disease transmission in the workplace (Gravina et al, 2020) injury prevention in sports (Quintero et al, 2020;Harris et al, 2020), physical activity (Nieto & Wiskow, 2020;Stedman-Falls & Dallery, 2020), cigarette smoking (Dallery et al, 2021), and health and wellness coaching (Finn & Watson, 2017;Normand & Bober, 2020). The strengths of behavior analysis (e.g., rigorous experimental methods, conceptual account of the causes of health behavior) increase the chances, but do not guarantee, that behavioral technology may lead to public health impact (Hantula, 2019).…”
Section: Do More Of What We Are Doingmentioning
confidence: 99%
“…In addition to the special series on public health in this journal, a 2019 special issue of Perspectives on Behavior Science focused on addictions, and showcased substantial basic, translational, applied, and public health contributions of behavior analysis (Washington & Galizio, 2019). Recent conceptual and empirical work has focused on diabetes prevention and management (Raiff et al, 2020), disease transmission in the workplace (Gravina et al, 2020) injury prevention in sports (Quintero et al, 2020;Harris et al, 2020), physical activity (Nieto & Wiskow, 2020;Stedman-Falls & Dallery, 2020), cigarette smoking (Dallery et al, 2021), and health and wellness coaching (Finn & Watson, 2017;Normand & Bober, 2020). The strengths of behavior analysis (e.g., rigorous experimental methods, conceptual account of the causes of health behavior) increase the chances, but do not guarantee, that behavioral technology may lead to public health impact (Hantula, 2019).…”
Section: Do More Of What We Are Doingmentioning
confidence: 99%
“…Firstly, these studies have demonstrated significant improvements in primary outcome measures. Secondly, improving health-related outcomes in chronic diseases is an ongoing, complex process heavily influenced by changes in health behaviors 31 , 32 . While digital twins can provide personalized health guidance based on individual health data, their impact on actual behaviors warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%